Assessment of sheep marketing system in Burie district, North Western Ethiopia - Abebe, Yenenesh; Melaku, S.; Tegegne, Azage (2013)
Assessment of the sheep marketing system was carried out through informal and formal surveys in selected kebeles and in selected sheep markets in Burie district in north western Ethiopia to assess the marketing system and to identify the constraints of sheep marketing in the area. The farmers interviewed in the selected kebeles for the informal survey were selected purposively and for the formal survey, by systematic random sampling method. In addition, three sheep markets namely Derequa, Burie and Kuche were selected and data were collected from these markets for this study. Farmers on average had 3.7 heads of sheep (n = 127, SD = 2.46) per household. On average, one household in the study area sold 1.1±1.40 heads of sheep (n = 127) per year. Farmers mainly sell sheep during Easter, New Year and Christmas. Sheep from Burie district and neighbouring districts and even neighbouring region enters into Burie district for marketing. Among the constraints identified in sheep marketing lack of market information service, sheep market price fluctuation during some months of the year, lack of market infrastructure and remoteness of markets to the producers that sell sheep were the main ones. To make improvements in sheep marketing system in Burie district, these constraints should be given more emphasis in research and development activities that are going to be undertaken in this area.